American heroes - Delano, Marfe Ferguson (Washington, D.C. : National Geographic, 2005)
Presents three hundred full-color photographs and archival illustrations that profiles fifty Americans in history including Pocahontas and Sacajawea, George Washington and Abraham Lincoln, Franklin Roosevelt, Martin Luther King, Rosa Parks, and many more.
Includes bibliographical references (p. 191) and index.
7.7
5-8
Keywords: Heroes -- United States -- Biography -- Juvenile literature; United States -- Biography -- Juvenile literature; Heroes; United States -- Biography; Heroes and heroines -- Biography; United States -- Biography